2011
DOI: 10.1123/jsep.33.5.649
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of the Attentional Networks at Rest vs. During Acute Bouts of Aerobic Exercise

Abstract: The present study explored the effects of three different activity conditions on three attentional functions: alerting, orienting, and executive control. A group of highly experienced cyclists performed the Attention Network Test-Interactions (Callejas, Lupiáñez, & Tudela, 2004) at rest, during moderate aerobic exercise, and during intense aerobic exercise. Results indicated that aerobic exercise accelerated reaction time and reduced the alerting effect compared with the rest condition. However, aerobic exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
61
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 45 publications
8
61
3
1
Order By: Relevance
“…The fact that previous studies have not found such an effect in young participants may be due to factors such as the type of exercise (acute instead of chronic in Huertas et al’s study [13]) or the insufficient amount of exercise practice by active participants [19].…”
Section: Discussionmentioning
confidence: 77%
“…The fact that previous studies have not found such an effect in young participants may be due to factors such as the type of exercise (acute instead of chronic in Huertas et al’s study [13]) or the insufficient amount of exercise practice by active participants [19].…”
Section: Discussionmentioning
confidence: 77%
“…In order to further identify the neural circuitry involved in the executive function, Rueda et al [26] had developed an integrated Attention Network Test (ANT) using flanker task [27] to measure the efficiency of three networks in adults. It showed that moderate aerobic exercise modulated the functioning of phasic alertness by increasing the general state of tonic vigilance [28], but aerobic exercise did not modulate the functioning of either the orienting or the executive control attentional networks. This may account for the dissimilar results based on other executive function tests, because these tests tap into the selective attention and orientation responses rather than into the conflict resolution process for interference.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research combining the investigation of different attentional networks have been performed only in the area of acute exercise research by adopting Posner and Petersen’s (1990) attention network test that combines in one task warning signals prior to targets (alerting), cues that direct attention toward potential target locations (orienting) and target stimuli surrounded by congruent or incongruent flankers (executive control; Huertas et al, 2011; Chang et al, 2015). Differently, the attentional test developed by Pesce et al (2003) and used for the present study merges typical features of the spatial orienting paradigm (Chica et al, 2014) with hierarchically built visual objects that contain global or local target features (Navon, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this special focus on PA effects on executive function is well justified, but has led, with specific regard to the PA-attention relationship, to a disproportional interest for the attentional networks responsible for executive control and to a relative neglect of the other attentional networks the executive control network is strictly intertwined with. The study of PA effects on attentional orienting is mainly limited to the effects of acute bouts of exercise in young active adults (Pesce et al, 2007b; Huertas et al, 2011; Sanabria et al, 2011; Luque-Casado et al, 2013; Chang et al, 2015; Llorens et al, 2015). The only two attentional orienting studies performed with older adults have tested the moderation of acute exercise effects by chronic PA participation (Pesce et al, 2007a, 2011).…”
Section: Introductionmentioning
confidence: 99%